University of the Philippines Mindanao IT equipment management system (ITEMS) inventory and report module - Ramirez, Prema Devii Baquiao (2011)
The University of the Philippines Mindanao IT Equipment Management System (ITEMS) is a web-based information management system that automates the operations of the Information Technology Office (ITO) regarding IT equipment units. ITEMS has modules for inventory management, report generation, equipment borrowing and equipment maintenance. Specifically, as developed in this study, the inventory module enables ITO to keep an electronic record of their equipment units and a mechanism to organize their equipment accounts' information, which involves adding equipment units and managing their updates and disposal history. The report generation module provides rapid and economical retrieval of all data transacted in the system featuring a user customizable requirement specifications interface to gather the report settings needed by the user. This also produces document format as a either PDF or CSV which can be opened with any spreadsheet applications. ITEMS is integrated as a sub-module under the administrative module of UP Mindanao Integrated Information Management System (UPMIIMS) through the ERP System.
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2011
Keywords: Inventory; Inventory management; Data retrieval; ERP system; Report generation; Report module; Information Technology Office (ITO); Spreadsheet applications; IT Equipment Management System (ITEMS); Inventory module; Equipment maintenance module